Problems Faced by Rural Women in Coastal Areas of Sindh, Pakistan - Imam Ud din Palal (Corresponding Author); Muhammad Ishaque; Ali Mustafa; Shahab Khan; Muhmmad Zaman; Inayatullah (`, 2025)
Rural women are pivotal contributors to agriculture, livestock, and fisheries worldwide, yet they remain among the most marginalized groups in terms of access to resources, education, and decision-making. In Pakistan, and particularly in Sindh’s coastal districts, these challenges are intensified by environmental degradation, sea intrusion, and entrenched socio-cultural barriers. This study examines the multifaceted problems faced by rural women in the Thatta and Badin districts of Sindh Province through a survey of 300 respondents selected via multistage cluster sampling. The findings reveal that most women have no formal education, possess limited access to modern technologies and agricultural extension services, and experience restricted participation in markets and community decision-making. Environmental hazards such as soil salinity, freshwater scarcity, and declining fisheries further destabilize household incomes. The study concludes that empowering rural coastal women requires gender-responsive agricultural policies, climate-resilient livelihood programs, and sustained investments in education, skills development, and institutional support. Keywords: Rural Women, Coastal Area Sindh, Gender Disparities, Economic Empowerment